Prevalence of diagnosed temporomandibular disorders among Saudi Arabian children and adolescents - Al-Khotani, Amal; Naimi-Akbar, Aron; Albadawi, Emad; Ernberg, Malin; Hedenberg-Magnusson, Britt; Christidis, Nikolaos (Journal of headache and pain, 2016)
Background Studies have indicated that the prevalence of symptoms and signs of temporomandibular disorders (TMD) are rare early in childhood, but become more prevalent in adolescents and adulthood. To our knowledge, no study has investigated the prevalence of TMD-diagnoses in children in the general population. The aim was thus to investigate the prevalence of TMD-diagnoses among children and adolescents in the general population using the Research Diagnostic Criteria for TMD (RDC/TMD). Methods The current cross-sectional study consisted of 456 children and adolescents, aged between 10 and 18, randomly enrolled from 10 boy’s- and 10 girl’s- schools in Jeddah. The participants first answered two validated questions about TMD-pain, followed by a clinical examination according to RDC/TMD. Results One hundred twenty-four participants (27.2 %) were diagnosed with at least one TMD-diagnosis. Myofascial pain was the most common diagnosis (15 %) followed by disc displacement with reduction, arthralgia, myofascial pain with limited mouth opening and osteoarthrosis. Children diagnosed with myofascial pain more often reported orofacial pain, headache and tooth clenching ( p < 0.05), whereas children with arthralgia more often reported orofacial pain and tooth grinding than those without a TMD-diagnosis ( p < 0.05). Only 18 % of the subjects in the TMD group had sought a dentist or physician for their pain. Conclusion TMD was common among children and adolescents in Saudi Arabia. Self-reported orofacial pain and headache as well as bruxism were associated with a TMD-pain diagnosis and disc displacement. A surprisingly low percentage of children and adolescents sought treatment by a dentist or physician for their pains.